2014
DOI: 10.1097/ncc.0b013e3182a40f99
|View full text |Cite
|
Sign up to set email alerts
|

“It’s Just Going to a New Hospital … That’s It.” Or Is It? An Experiential Perspective on Moving From Pediatric to Adult Cancer Services

Abstract: The findings provide a meaningful framework to understand the experience of transition from the perspective of young people, parents, and healthcare professionals. These findings could help with the planning and preparation of individualized transitional care pathways for survivors of childhood cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…The tools are useful in identifying areas in which an individual survivor needs more support or education. The most frequently identified barriers to transition in these publications related to knowledge, education and empowerment of the survivors as well as the knowledge and education of healthcare providers (193,194,(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223). This highlights that education of both survivors and their healthcare providers is integral part of successful transition.…”
Section: Transition From Paediatric To Adult Hsct Carementioning
confidence: 99%
“…The tools are useful in identifying areas in which an individual survivor needs more support or education. The most frequently identified barriers to transition in these publications related to knowledge, education and empowerment of the survivors as well as the knowledge and education of healthcare providers (193,194,(212)(213)(214)(215)(216)(217)(218)(219)(220)(221)(222)(223). This highlights that education of both survivors and their healthcare providers is integral part of successful transition.…”
Section: Transition From Paediatric To Adult Hsct Carementioning
confidence: 99%
“…Their descriptions included lack of information about late effects, how to handle those and limited understanding from their surrounding networks, as well as from health care professionals conducting follow-ups (Hauken, et al, 2013). Meeting reality can also include the transition from the paediatric care setting to an adult care setting, something which can be experienced very differently among individuals and include many perspectives and dimensions (McCann, Kearney, & Wengström, 2013).…”
Section: Being Diagnosed With Cancer As a Childmentioning
confidence: 99%
“…Therefore, good QoL helps parents to give good care for children. Findings from qualitative pieces of research suggested there was a necessity to pay attention to QoL of parents during transitional period (McCann et al., 2014; Paine et al., 2014). QoL of parents with children having long‐term conditions often contain the physical, emotional, social and cognitive functioning dimensions (Varni et al., 2004), that are influenced by children (Moreira et al., 2013).…”
Section: Introductionmentioning
confidence: 99%